Determinasi Indeks Pembangunan Manusia di Provinsi Pulau Jawa (Pendekatan Data Panel Tahun 2015-2024) - Meyva Dita Lutvi Angraini (Jurnal Pendidikan Ekonomi Undiksha, 2026)
The Human Development Index (HDI) in the provinces of Java Island shows persistent disparities despite the region's dominant role as Indonesia’s economic center. This study analyzes the determinants of HDI, namely government expenditure, unemployment rate, number of micro industries, and labor absorption in six provinces of Java Island during 2015–2024. Using secondary data from the Central Bureau of Statistics (BPS), the research employs panel data analysis with model selection through the Chow, Hausman, and Lagrange Multiplier tests. The Fixed Effect Model was selected as the most suitable model. Hypothesis testing was conducted using the t-test, F-test, and coefficient of determination (R²). The results indicate that government expenditure, micro industries, and labor absorption positively and significantly influence HDI, while unemployment has a negative effect. Simultaneously, all independent variables significantly influence HDI. The findings highlight that improvements in human development in Java Island are shaped byeffective public spending, labor market conditions, and the growth of micro industries.